Investigating metacognitive planning in collaborative problem-solving among undergraduate mathematics education students - Jamil, Anis Farida; Fatmanissa, Namirah (Metaverse: Journal of Mathematics Teacher Professional Development Research, 2026)
Planning is one of the crucial components of metacognitive regulation. However, metacognitive planning is less studied empirically. This case study aims to explore the metacognitive planning activities of students when collaboratively solving mathematical problems. Proof problems in geometry were given to eight groups willing to participate in the research. Each group consisted of two undergraduate mathematics education students. Group discussion activities in solving problems were recorded using video-audio recorders. Interviews were also conducted with the groups to obtain more data on the metacognitive planning activities, thus achieving the research objectives. This study identified three different characteristics of metacognitive planning. We labelled these three planning characteristics as high, middle, and low levels of metacognitive planning. The low-level planning entails the formulation of a single problem-solving plan. Middle-level planning involves the formulation of two problem-solving plans, albeit the selection of the appropriate plan occurs through trial and error. Conversely, the formulation of more than two problem-solving plans and the ability to select the most effective plan characterize high-level planning. These findings can be utilized by educators to assess the efficacy of their students’ metacognitive planning activities as a learning outcome.